Longitudinal tracking of muscular power changes of NCAA Division I collegiate women gymnasts - French, D. N.; Gomez, A. L.; Volek, J. S.; Rubin, M. R.; Ratamess, N. A.; Sharman, M. J.; Gotshalk, L. A.; Sebastianelli, W. J.; Putukian, M.; Newton, R. U.; Häkkinen, K.; Fleck, S. J.; et al. (The Journal of Strength and Conditioning Research, 2004)
Gymnastics relies upon power as a critical component of sports-specific fitness. The purpose of this study was to monitor long-term training adaptations in the power of National Collegiate Athletics Association Division I women gymnasts. Twenty members of a women's gymnastic team (aged 18-22) were tracked over 3 years with the first year a baseline year of testing. Whole body power for the counter-movement (CMJ) and squat (SJ) vertical jump was obtained via force plate analyses at 2 assessment time points during each year (February and November). Results showed significant (p 0.05) and continued increases in peak power output in the CMJ and SJ at each biannual assessment. Improvements of 46% (+1010 W) for the CMJ and 43% (+900 W) for the SJ were observed at the end of the tracking period. Peak power for the CMJ and SJ were recorded at 3210 W (±350 W) and 3000 W (±152 W), respectively. Associated improvements in the time to peak power of 36% (-0.239 second) and 38% (-0.151 second) were also found for the CMJ and SJ. There were no significant changes in body mass or total skinfold thickness, however, a shift toward improved fat free mass (i.e., lean muscle mass) was apparent. These data underscore the importance that specificity, and more importantly power development, should play in the conditioning of collegiate women gymnasts' training programs.